Enzyme immobilization on silicate glass through simple adsorption of dendronized polymer–enzyme conjugates for localized enzymatic cascade reactions1. Issue 55 (17th June 2015) - Küchler, Andreas; Adamcik, Jozef; Mezzenga, Raffaele; Schlüter, A. Dieter; Walde, Peter
<x xml:space="preserve">Abstract</x> Conjugation of enzymes to a dendronized polymer via bis-aryl hydrazone bonds enables simple and stable enzyme immobilisation on unmodified glass.